Jumping translocation in a case of De novo infant acute myeloid leukemia. Issue 2 (9th September 2013) - Parihar, Mayur; Gupta, Anurag; Yadav, Anil Kumar; Mishra, Deepak Kumar; Bhattacharyya, Arpita; Chandy, Mammen
Abstract An infant presented with fever and purulent discharge from the left ear, proptosis of the right eye, and hepatosplenomegaly. She was diagnosed with acute monoblastic leukemia on morphological and flowcytometric analysis of the bone marrow. Karyotyping showed a jumping translocation (JT) involving the long arm of chromosome 1 as the sole cytogenetic abnormality in 29 metaphases. The patient died within 2 months of diagnosis. The presence of JT in a de novo infant AML as a sole cytogenetic abnormality indicates its possible role in leukemogenesis unlike previous reports that have implicated its role in tumor progression only. Pediatr Blood Cancer 2014;61:387–389. © 2013 Wiley Periodicals, Inc.